Associação da percepção da qualidade de vida, nível de atividade fisica e comportamentos relacionados à saúde em escolares adolescentes - Gustave, Eva Luziane Denkewicz (2023)
Objective: To analyze the association between health-related behaviors and perceived quality of life among schoolchildren aged 10 to 15 years after the period of social isolation due to the Covid-19 pandemic. Methodology: This study presents a quantitative approach with a cross-sectional descriptive exploratory design, carried out with an intentional sample of 330 schoolchildren aged 10 to 15 years of both genders in a public school in Curitiba, Paraná. For data collection in June 2022, the following instruments were used: WebCas questionnaire (composed of seven segments), KIDSCREEN-52 (with 52 questions in 10 dimensions) and a questionnaire for the characteristics of the sample. The data were stored in the database and later exported to an Excel spreadsheet, which were treated and categorized/dichotomized for the subsequent data analysis. Then the procedures of descriptive statistics, frequency distribution, chi-square association tests and binary logistic regression were adopted, considering the significance level p=≤0.05, using the statistical software (SPSS 20.0). Results: 85.2% (n=281) of participants were classified with perceived low quality of life. The prevalence of inappropriate behaviors was high, insufficient level of physical activity (85.2%), passive commuting to school (79.4%), high time in front of screens (69.1%), inadequate hours of sleep during the week (54.3%), low consumption of fruits (57.8%) and vegetables (51.2%). We observed a significant negative association between low perceived quality of life and inadequate time in front of screens (x²=8.79; p=0.001), inadequate consumption of fruits and vegetables (x²=3.97; p=0.04) and (x²=3.56; p=0.05) and alcohol consumption (x²=3.85; p=0.05). When stratified by gender, low perceived quality of life was associated with female gender (x²=5.31; p=0.02). Passive commuting was statistically associated with school-goers classified in the high socioeconomic stratum (x²=6.71; p=0.01) and with ages 10 and 11 years (x²=19.27; p=0.001). The school-aged children classified as having inadequate fruit consumption were significantly associated with the low sócio-economic stratum (x²=8.78; p=0.001). On the other hand, the students classified with episodes of drunkenness (x²=7.12; p=0.02), alcohol consumption (x²=10.34; p=0.001) and perception of low quality of life (x²=12.10; p=0.001) were significantly associated to 12 and 13 years old. The variable that proved to be predictive in perceived quality of life was screen time (OR=0.42; CI=0.22 – 0.81), when stratified by gender no significant result was obtained in females, but in males, the variable fruit consumption (OR=2.28; CI= 1.06-4.92) proved predictive and referring to pre-pubertal maturation status indicates that fruit consumption (OR: 3.69; CI= 1.30-10.47) and soft drinks (OR: 4.10; CI= 1.40-12.02) were statistically predictive. Final considerations: It was concluded that the prevalence of health-related behaviors classified as inappropriate was higher among females, as well as that girls showed a high prevalence of scores classified as low perception of quality of life. Quality of life showed a significant association with age, gender and maturation status.